THE DEFINITION OF MINIMUM NECESSARY DIMENSIONS OF THE DETECTION SYSTEMS OF SECURITY TELEVISION MONITORING ON INFORMATIZATION OBJECTS - Igor Vladimirovich Kaliberda (Современная наука и инновации)
The geometrical dimensions of the detection systems of security television monitoring should be optimal for such tasks as intruder detection, recognition of known person, recognition of an unknown person and so on.The solution, allowing determining the minimum required parameters when building this system, is proposed. It is shown that the sizes of the detection regions depend on the configuration of the protected object information, the technical characteristics of the system of television supervision and tasks of the system. The decision is considered on the basis of requirements of normative documents by using the simulation method.